Impact of Clinical Specialty on Attitudes Regarding Overuse of Inpatient Laboratory Testing. Issue 12 (27th June 2018) - Korenstein, Deborah; Husain, Solomon; Gennarelli, Renee L; White, Cilian; Masciale, James N.; Roman, Benjamin R.
Abstract : Routine laboratory testing is common among hospitalized patients, with associated harm. Attitudes toward testing and drivers across clinical specialties have not been described. We performed a cross‐sectional study and anonymously surveyed inpatient clinicians (nurses, advanced practice providers, and physicians) at a tertiary cancer center regarding attitudes toward unnecessary laboratory testing and its drivers across clinical specialties. A total of 837 providers completed surveys (response rate 53%). Most respondents agreed with daily testing of hospitalized patients and that daily labs generally enhance safety, and those from pediatric and surgical specialties generally valued testing less than others. Participants most commonly identified habit and institutional culture as important drivers of unnecessary testing. There were differences in other drivers across specialties, with pediatric clinicians identifying family pressure more commonly and fear of litigation less commonly compared to others. Future interventions to reduce unnecessary inpatient laboratory testing should acknowledge different attitudes based on specialty and tailor interventions accordingly.